SBAs and EMQs in paediatrics for medical students - Sharma, Neel. (BOCA RATON : CRC Press, 2010)
Dr Sharma has definitely mastered the art of producing a comprehensive, evidence-based review tool of core paediatric knowledge whilst at the same time appealing to a broad audience, which in my opinion is quite a remarkable achievement. You're definitely looking at an invaluable resource and buying this book will help you to rise up to the challen
OCLC-licensed vendor bibliographic record.
Keywords: Pediatrics -- Examinations, questions, etc; MEDICAL / General